(3TQM geRjI GdHhUjQis - (3eMeO Hf eMeO MLi RfjHQ GdSdhis; (3eMeO Hf SYjO Hf MeGO GdUfgGLj GdHhUjQj, (B696 (3g`,J (B696 (3g` s
(3ChdgG (B:s
(3hChd eG LGA ajg (B: (3abGd (B: (3GQi cd eOM ajg GdfHi ebUQkG hEf HGdZ GdeKfi Ydjg hCcKQkG s
(3BNQgG (B:s
(3HLGg UGMHgG GdeYXe CQJLi ScGfi ai OGQ GdcQGeI hGdfYe s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B11s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B253 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3MGdI GdfSNI LjOI s
Keywords: (3GdJGQjNs